Clinical outcomes in transient epileptic amnesia: A 10‐year follow‐up cohort study of 47 cases. Issue 5 (18th March 2022) - Savage, Sharon A.; Baker, John; Milton, Fraser; Butler, Christopher; Zeman, Adam
Abstract: Objective: Transient epileptic amnesia (TEA) is a form of adult‐onset epilepsy where presenting features are well described, but little is known regarding prognosis. This study aimed to elucidate the long‐term prognosis of TEA regarding seizure control, memory, medical comorbidities, and life expectancy. Methods: Up‐to‐date clinical information was collected for 47 people diagnosed with TEA who had joined the The Impairment of Memory in Epilepsy (TIME) study 10 years earlier. At entry to the study, information about comorbid conditions was systematically collected. Details regarding subsequent diagnoses, seizure activity, changes to treatment, or reports of cognitive impairment were obtained through the family doctor. The variables of interest were compared with UK population data. Results: Mortality in the cohort was 21 of 47 (45%), with an average age at death of 82.5 years. Seizures remained well controlled for the majority but medications required adjustments in dose and type for some (28%). A small number (three cases) remained seizure‐free without medication. History of cardiovascular disorders was frequent (78.7%), typically involving hypertension (55.3%). Autoimmune disorders (25.5%), cancer (23.4%), and depression (21.3%) were also commonly reported. Although persisting memory problems were often noted, dementia was diagnosed in seven cases (14.9%). Life expectancy and comorbidities in TEA did not differ from available population norms. Significance: Results suggest that life expectancy is not reduced in TEA. Although TEA does not appear to be a self‐limiting form of epilepsy, seizures are typically well controlled via medication. Because adjustments to medication may be required, even after long periods of stability, ongoing medical monitoring is recommended. Comorbid vascular disorders are frequent but appear similar to general population estimates. Monitoring mood may be important, given that people with chronic conditions are often vulnerable to depression. Because of persisting memory difficulties, the development of effective memory interventions for people with TEA is warranted.